Answer:
y = [tex]-\frac{1}{5}x[/tex] - 4
Step-by-step explanation:
As we know the point slope form of an equation is as follows -
y - y₁ = m ( x - x₁ )
As we have slope , m = [tex]-\frac{1}{5}[/tex]
And point (x₁ , y₁ ) = ( -5, -3)
⇒ y - ( -3) = [tex]-\frac{1}{5}[/tex] ( x - (-5) )
⇒ y + 3 = [tex]-\frac{1}{5}[/tex] ( x + 5 )
⇒ y + 3 = [tex]-\frac{1}{5}[/tex] x - 1
⇒ y = [tex]-\frac{1}{5}[/tex] x - 1 - 3
⇒ y = [tex]-\frac{1}{5}[/tex] x - 4
So, the equation becomes
y = [tex]-\frac{1}{5}x[/tex] - 4